Improved Segmentation for Intravascular Ultrasound (IVUS) Modality - Beeran Kutty, Suhaili; Wirza O.K Rahmat, Rahmita; Shahlan Kassim, Sazzli; Madzin, Hizmawati; Hamdan, Hazlina (International Journal of Engineering and Technology, 2018)
IVUS is the modality to investigate the internal structure of the coronary artery. Segmentation is necessary to differentiate the lumen, the media-adventitia and others feature that appears on the modality, but manual segmentation is tedious and time-consuming. To enhance the computational segmentation, this paper presents the process to segment catheter shape, inner and outer layer of the artery. The new algorithm is proposed to detect the catheter shape and percentage of the accuracy is 100%. We also provide information on detection of lumen and media-adventitia border and area using a parametric deformable model algorithm with gradient vector flow as the external force. The Percentage Area of Difference (PAD) value for the segmentation is below than one, indicate that this proposed method is highly encouraging for IVUS segmentation process. Based on the inner border detected, media-adventitia boundaries also can be detected without manual initialization points. This work is important to facilitate the process of the 3D reconstruction of the coronary artery.Â